2006
DOI: 10.1001/archsurg.141.7.655
|View full text |Cite
|
Sign up to set email alerts
|

Acute Respiratory Distress Syndrome in the Trauma Intensive Care Unit

Abstract: Hypothesis: The diagnosis of acute respiratory distress syndrome (ARDS) carries significant additional morbidity and mortality among critically injured patients. Design: Retrospective case-control study using a prospectively maintained ARDS database. Setting: Surgical intensive care unit (ICU) in an academic county hospital. Patients: All trauma patients admitted to the ICU from January 1, 2000, to December 31, 2003, who developed ARDS as defined by (1) acute onset, (2) a partial pressure of arterial oxygen-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
56
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 30 publications
7
56
0
Order By: Relevance
“…4,6,7 A recent study of ARDS in trauma patients reported a mortality rate of 28%. 35 The overall mortality rate in the present study, with the use of prone or supine kinetic therapy, was 30%, but was only 19% when deaths from head injury were excluded. This study also demonstrated a modest survival benefit to prone versus supine positioning with kinetic therapy.…”
Section: Discussionmentioning
confidence: 48%
“…4,6,7 A recent study of ARDS in trauma patients reported a mortality rate of 28%. 35 The overall mortality rate in the present study, with the use of prone or supine kinetic therapy, was 30%, but was only 19% when deaths from head injury were excluded. This study also demonstrated a modest survival benefit to prone versus supine positioning with kinetic therapy.…”
Section: Discussionmentioning
confidence: 48%
“…ARDS increases the median duration of mechanical ventilation [37], which can be correlated with longer ICU stays. In trauma patients, ARDS is associated with longer hospital and ICU LOS, and increased morbidity, as well as costs, whereas mortality is not affected [38]. In blunt trauma, independent risk factors for ARDS were ISS ≥25, pulmonary contusion, age ≥65 years, hypotension on admission and massive transfusion [39].…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects have recently been noted in the trauma literature as a decrease in the incidence, morbidity, and mortality of ARDS in the trauma population. 1820 Previous modes of ventilatory support were shown to incite barotrauma and accentuate the host inflammatory response, which likely compounded the initial damage caused by inhalation injury.…”
Section: Discussionmentioning
confidence: 99%